Pengaruh Fasilitas Terminal Keberangkatan terhadap Kepuasan Pengguna Jasa di Bandar Udara Radin Inten II Lampung - Muhamad Shazif; Dhiani Dyahjatmayanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The commitment of the Indonesia government to prioritize the development of tourism and aviation as the focus of regional economic growth is reflected in various strategic policies and programs. In line with this, Radin Inten II Lampung Airport always strives to improve facilities, especially in the departure terminal area. This study aims to understand the influence of departure terminal facilities on passenger satisfaction at Radin Inten II Airport Lampung. This research was conducted using a quantitative approach, where data was collected through questionnaires and literature studies. Instrument feasibility analysis using validity test, reliability test, data analysis using normality test, simple linear regression analysis, t-test and determination coefficient analysis (R2). The results of the study showed that departure terminal facilities had an effect on service user satisfaction at Radin Inten II Lampung Airport with a value of 0.51 or 51%, which meant that the independent variable (departure terminal facilities) affected the dependent variable (service user satisfaction) by 51% and the remaining 49% was influenced by other factors that were not in this study.